The Long-run Economic Costs of AIDS : Theory and an Application to South Africa - Bell, Clive (World Bank, Washington, DC, 2014)
Most existing estimates of the macroeconomic costs of AIDS, as measured by the reduction in the growth rate of gross domestic product, are modest. For Africa-the continent where the epidemic has hit the hardest-they range between 0.3 and 1.5 percent annually. The reason is that these estimates are based on an underlying assumption that the main effect of increased mortality is to relieve pressure on existing land and physical capital so that output per head is little affected. The authors argue that this emphasis is misplaced and that, with a more plausible view of how the economy functions over the long run, the economic costs of AIDS are almost certain to be much higher. Not only does AIDS destroy existing human capital, but by killing mostly young adults, it also weakens the mechanism through which knowledge and abilities are transmitted from one generation to the next. The children of AIDS victims will be left without one or both parents to love, raise, and educate them. The model yields the following results. In the absence of AIDS, the counterfactual benchmark, there is modest growth, with universal and complete education attained within three generations. But if nothing is done to combat the epidemic, a complete economic collapse will occur within three generations. With optimal spending on combating the disease, and if there is pooling, growth is maintained, albeit at a somewhat slower rate than in the benchmark case in the absence of AIDS. If pooling breaks down and is replaced by nuclear families, growth will be slower still. Indeed, if school attendance subsidies are not possible, growth will be distinctly sluggish. In all three cases, the additional fiscal burden of intervention will be large, which reinforces the gravity of the findings.